Pemanfaatan Tumbuhan Liar Berbunga untuk Konservasi Musuh Alami Serangga di Ekosistem Kelapa Sawit di Lahan Sub-Optimal Sumatera Selatan - Ghani Prabawati; Siti Herlinda; Yulia Pujiastuti; Tili karenina (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2017)
Prabawati et al, 2017. The Role of Wild Flowering Plants in Conserving Insect Natural Enemies in Lowland Oil-Palm Ecosystem of South Sumatera. JLSO 6(1):78-86.Wild flowering plants can be used in increasing the potential of insect natural enemies on oil palm plantations. This paper inventoried the diversity of natural enemies that interacted with wild flowering plants in the oil palm ecosystem. Wild flowering plants are used as feed sources and living places Â which provide alternate hosts for natural enemies, namely predators and parasitoids. Some families of flowering plants associated withÂ parasitoids in oil palm ecosystem include Euphorbiaceae, Leguminosae, Fabaceae, Acanthaceae, Asteraceae, Polygonaceae, Rubiaceae, Capparidaceae, Lamiaceae, Turneraceae. Some plant species associated with predators in oil palm plantations include Antigonon leptosus, Elephantopus tomentosus, Nephrolepis biserata.